Intraocular toxicity caused by MEROCTANE perfluorocarbon liquid - Coco-Martin, Rosa M.; Andres-Iglesias, Cristina; Srivastava, Girish K.; Lagos-Rodriguez, Javier; Ruiz-Tevah, Miguel; Diaz-Cardenas, Mario R.; Fernandez-Bueno, Ivan; Garcia-Serna, Juan; Garcia-Gutierrez, Maria T.; Garcia-Layana, Alfredo; Carlos Pastor, J. (My University, 2021)
Serious intraocular toxicity cases have been reported worldwide after the use of different perfluorocarbon liquids. The current study reports for the first-time the clinical pictures of cases of acute intraocular toxicity caused by MEROCTANE, a perfluoro-octane commercialized by a Turkish company and distributed in many countries. A series of 18 cases from Chile and Spain was retrospectively analysed. To evaluate the impurity profile, a suspicious MEROCTANE sample (lot OCT.01.2013) was analysed by gas chromatography mass spectrometry and compared with a non-suspicious sample of the same commercial perfluoro-octane (lot OCT 722011). Cytotoxicity was tested following a direct-contact method, taking into consideration the high volatility and hydrophobicity of perfluoro-octane and following the ISO 10993 guideline. Cytotoxicity test showed clear cytotoxic effects of the analysed batch (less than 9% of cell viability). Moreover, chemical analysis demonstrated the presence of many contaminants, some highly toxic (acids and alcohols). Perfluorocarbon liquids are useful tools for intraocular surgery but companies and Agencies of Medical Devices must implement measures that guarantee the safety of these products based on both chemical and cytotoxicity analysis for every batch. Medical staff should be encouraged to report any suspected case to their respective National Agencies.
Keywords: Guideline